Ireland : Financial Sector Assessment Program: Technical Note-Update on the Assessment of Implementation of the IOSCO Objectives and Principles of Securities Regulation. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for implementation of the International Organization of Securities Commissions Objectives and Principles of Securities Regulation in Ireland. Since 2013, the regulation of securities and associated institutions and markets has witnessed considerable innovation in Ireland. As in other supervisory areas, the central bank has dedicated more staff to the supervision of securities and taken a more proactive approach. The central bank has also developed innovative ongoing systemic analysis. Certain issues raised in the 2013 assessment have not been addressed, in large part because any action would require amendments to primary legislation or EU structures or other changes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet